1995
DOI: 10.1111/j.1399-0004.1995.tb03960.x
|View full text |Cite
|
Sign up to set email alerts
|

Periumbilical skin length measurements in the newborn

Abstract: Normal limits of periumbilical skin were determined in 304 newborn babies in the first 24 h. Cranial umbilical skin (SD) was 12.36 (3.23) mm and caudal umbilical skin (SD) was 8.76 (3.10) mm on the average. It is recommended that cranial umbilical skin measurement should be included in the examination of dysmorphic neonates, and those with cranial skin length above 18.82 mm (>2 SD) should be carefully evaluated for Rieger syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Cullen described 60 variants of the umbilicus, which he classified into nine groups through examining 200 individuals, none of whom had redundant umbilical or peri-umbilical skin (2). The umbilical skin length is usually measured using a standard metal compass while applying gentle traction to the cord (9,10). O'Marcaigh et al studied the umbilical skin length in 104 neonates and the results were further confirmed by Toppare et al who studied 304 neonates (9, 10).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Cullen described 60 variants of the umbilicus, which he classified into nine groups through examining 200 individuals, none of whom had redundant umbilical or peri-umbilical skin (2). The umbilical skin length is usually measured using a standard metal compass while applying gentle traction to the cord (9,10). O'Marcaigh et al studied the umbilical skin length in 104 neonates and the results were further confirmed by Toppare et al who studied 304 neonates (9, 10).…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, prominent and redundant umbilical skin has been almost exclusively described in the setting of Rieger syndrome in which it represents a core feature in conjunction with hypodontia and goniodysgenesis (7,8). Based on these results, Toppare et al recommended that a newborn with cranial umbilical skin length exceeding 18.82 mm [2 SDs above the mean (12.36 mm)] be evaluated for the presence of Rieger syndrome (10). Failure of umbilical skin to involute is believed to be the defect leading to this abnormality, so it is not a variant of umbilical hernia or other ventral body wall defects (7).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations